ADM1 based mathematical model of trace element complexation in anaerobic digestion processes. (March 2019) - Maharaj, Bikash Chandra; Mattei, Maria Rosaria; Frunzo, Luigi; Hullebusch, Eric D. van; Esposito, Giovanni
Graphical abstract: Highlights: TE complexation and precipitation processes were modelled concurrently in ADM1. TE speciation among complexes and precipitates was simulated. EDTA competed with sulfide and improved TE bioavailability. With sub-optimal TE concentration, EDTA stimulates higher rate of CH4 production. Effect of addition of Ca and Mg on TE-EDTA complexation was studied. Abstract: In this study, a new model based on anaerobic digestion model no.1 (ADM1) approach has been proposed to simulate trace elements (TEs) complexation, precipitation and their effect on the anaerobic batch methane production. TEs complexation reactions with VFAs and EDTA have been incorporated in an extended ADM1 model which considers TE precipitation/dissolution reactions as well as biodegradation processes. The kinetic model tracks the dynamics of 90 state variables which constitute the components of the proposed anaerobic digestion (AD) model. The incorporation of the complexation reactions required the definition of new inorganic components (EDTA species) and new complexation process rates in the ADM1 framework. The charge balance was modified accordingly to consider the effects of the additional components. The new model is able to predict: a) the effect of TE-EDTA/VFA complexation on methane production, and b) the effect of the initial calcium and magnesium concentrations on process performance.